2019
DOI: 10.1111/ahg.12310
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphisms in TPM1 rs11071720, rs3803499, rs12148828, and rs1972041 with the risk of nonsyndromic cleft lip with or without cleft palate in a sample of the Iranian population, a preliminary report

Abstract: Several lines of evidence support an association between tropomyosin 1 (TPM1) and the risk of nonsyndromic cleft lip with or without cleft palate (NSCL/P). The present study aimed to investigate the association between TPM1 polymorphisms and the risk of NSCL/P in an Iranian population. This case-control was done on 105 NSCL/P patients and 110 unrelated healthy controls. TPM1 rs11071720, rs3803499, rs12148828, and rs1972041 polymorphisms were genotyped by the polymerase chain reaction-restriction fragment lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A Single Nucleotide Polymorphism (SNP) is a replacement of a nucleotide at several positions in the human genome (Kitts and Sherry, 2002). Studies by Dr. Hashemi's research team showed that there had been relationships between SNPs and different diseases, including breast cancer (Hassanzarei et al, 2017), prostate cancer (Hassanzarei et al, 2017;Sattarifard et al, 2019), lung cancer , colorectal cancer , bladder cancer (Sadeghi-Bojd et al, 2019), nephrotic syndrome (Sadeghi-Bojd et al, 2019), nonsyndromic cleft lip (Rafighdoost et al, 2015;Rafighdoost et al, 2017;Rafighdoost et al, 2018;Rafighdoost et al, 2019), and nonalcoholic fatty liver disease (Hashemi et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…A Single Nucleotide Polymorphism (SNP) is a replacement of a nucleotide at several positions in the human genome (Kitts and Sherry, 2002). Studies by Dr. Hashemi's research team showed that there had been relationships between SNPs and different diseases, including breast cancer (Hassanzarei et al, 2017), prostate cancer (Hassanzarei et al, 2017;Sattarifard et al, 2019), lung cancer , colorectal cancer , bladder cancer (Sadeghi-Bojd et al, 2019), nephrotic syndrome (Sadeghi-Bojd et al, 2019), nonsyndromic cleft lip (Rafighdoost et al, 2015;Rafighdoost et al, 2017;Rafighdoost et al, 2018;Rafighdoost et al, 2019), and nonalcoholic fatty liver disease (Hashemi et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…Existing studies on the influence of TPM1 gene in the development of non syndromic cleft lip and palate have established some association between a few SNP and NSCL/P in different ethnic population (23)(24)(25)(26). SNPs rs1972041GA, rs197204, rs11071720, rs3803499, rs 1873147 and rs12148828 were studied in the Chinese population for its influence in the development of NSCL/P (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…SNPs rs1972041GA, rs197204, rs11071720, rs3803499, rs 1873147 and rs12148828 were studied in the Chinese population for its influence in the development of NSCL/P (24,25). SNPs rs11071720, rs12148828, rs3803499 and rs1972041 have been evaluated for association NSCL/P in the Iranian polymorphism (23). European-descent population-based studies found significant associations between isolated cleft lip only and fetal SNPs near TPM1 gene (26).…”
Section: Introductionmentioning
confidence: 99%